Understanding muzaki adoption of digital zakat payments in Indonesia - Emiroh Arsyina Ahimsa; Heri Sudarsono; Muhammad Abdul Ghoni; Muchammad Taufiq Affandi (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – This study aims to analyze the influence of performance expectancy, effort expectancy, social influence, zakat literacy, and facility conditions on the intention of muzaki to pay zakat using a digital platform.Methodology – Primary data was collected through an online survey involving 144 Jawa. Muzaki has used various online channels to pay zakat and analyzed it using structural equation modeling as the empirical approach. This study used the extended unified theory of acceptance and use of technology (UTAUT) as the theoretical framework. The data analysis technique used in this study is partial least square (PLS) analysis.Findings – The findings indicate that performance expectancy, effort expectancy, social influence, and zakat literacy have a positive influence on the intention of Muslims to pay zakat through online platforms. Meanwhile, the intention to pay zakat and facility conditions have a positive influence on the use of online platforms to pay zakat.Implications – Zakat institutions need to improve digital facilities to make it easier for muzaki to pay zakatOriginality – The object of this research focuses on Muslim communities on the island of Java who have fulfilled the requirements as muzaki.